Penggunaan Tata Bahasa Present Perfect Tense yang Tepat dalam Kalimat Bahasa Inggris - Putri, Salma Maulidia; Putri, Alya Maulida (Universitas Djuanda, 2025)
English as a foreign language has a very important role in the development of science, education, arts and culture, especially in the era of globalization. Its existence has a significant impact on learning which is beneficial for both social and academic aspects. Present perfect tenses are used to express events that occurred in the past, but are still relevant or continuing today. The purpose of the present perfect tense is to clarify an event that occurred before an event in the past. This research is a descriptive method with a literature review taken from previous sources. As a result, we can understand more about the verb